Les verbes à suffixe libre et l’expressivité - Kaliska, Agnieszka (Verbum – Analecta Neolatina, 2006)
The purpose of the paper is to consider how a free suffix can affect the semantics of verbs. The morphemes in question, which are considered free of semantic function and morphologically autonomous, are highly productive in verbal communication. Interestingly, the morphological structure of some verbs contains two free suffixes. In fact, the morphological and semantic autonomy contribute to the increase in the number of synonyms and stylistic variants. The paper suggests that free suffixes are highly charged. Their expressivity is their most important semantic function.